Effects of dietary pomegranate seed pulp on oxidative stability of kid meat. (June 2015) - Emami, A.; Nasri, M.H. Fathi; Ganjkhanlou, M.; Zali, A.; Rashidi, L.
Abstract: This study was conducted to evaluate the effects of dietary pomegranate seed pulp (PSP) on meat color and lipid stability of kids. Thirty-two Mahabadi male kids were randomly assigned to one of four diets with different levels of PSP: 1 — diet without PSP (Control), 2 — diet containing 5% PSP (PSP5), 3 — diet containing 10% PSP (PSP10), and 4 — diet containing 15% PSP (PSP15). The kids were slaughtered at the end of the study and m. longissimus lumborum (LL) was sampled. The TBARS values of both raw and cooked meat were decreased ( P < 0.0001) by increasing levels of PSP in the diet. The meat of kids fed PSP15 showed higher a* and C* values ( P < 0.01) and lower H* and b* values ( P < 0.001), than kids fed with Control diet. The results of this experiment indicated that replacing barley and corn grains with PSP in the diet may improve the color and lipid stability of kid meat. Highlights: Pomegranate seed pulp (PSP) as a by-product feedstuff in kid diet was evaluated. PSP decreased lipid oxidation and improved color stability of kid meat. PSP was found to be a cost effective antioxidant rich feedstuff for ruminant nutrition.